Integration Analysis of Pharmacokinetics and Metabolomics to Predict Metabolic Phenotype and Drug Exposure of Remdesivir - Du, Ping; Wang, Guoyong; Hu, Ting; Li, Han; An, Zhuoling (Frontiers in Pharmacology, 2022)
Remdesivir has displayed pharmacological activity against SARS-CoV-2. However, no any pharmacometabolomics (PM) or correlation analysis with pharmacokinetics (PK) were revealed. Rats were intravenously administered remdesivir and series of blood samples were collected before and after treatment. Comprehensive metabolomics profile and PK were investigated and quantitated simultaneously using our previous reliable HPLC-MS/MS. Both longitudinal and transversal metabolic analysis were conducted, and correlation between PM and PK parameters were performed using Pearson correlation analysis and PLS model. Multivariate statistical analysis was employed for discovering candidate biomarkers which predicted drug exposure or toxicity of remdesivir. The prominent metabolic profiles variation was observed between the pre- and post-treatment, and significant changes were found in 65 metabolites. A total of 15 metabolites-12 carnitines, one N-Acetyl-D-glucosamine, one Allantoin and one Corticosterone-were significantly corelated with concentration of Nuc (active metabolite of remdesivir). Adenosine, Spermine, Guanosine, sn-glycero-3-Phosphocholine, and L-homoserine may be considered potential biomarkers for predicting drug exposure or toxicity. This study is the first attempt to apply PM and PK to study remdesivir response/toxicity, and the identified candidate biomarkers might be used to predict the AUC and Cmax, indicating capable of discriminating good or poor responders. Presently, this study originally offers considerable evidences to metabolites reprogramming of remdesivir, and shed light on precision therapy development in fighting COVID-19.